Grandville. Force majeure : a fantasy - Talbot, Bryan (Talbot, Bryan. Detective-Inspector Lebrock of Scotland Yard scientific-romance thriller., 2017)
"Wanted for murder and on the run, Detective Inspector LeBrock is the victim of a diabolical scheme engineered by gangland overlord Tiberius Koenig. But LeBrock is a fighter, and now against insurmountable odds the British Badger risks all to thwart Koenigs plot and save Queen, country, and all he loves!"--Amazon.com.